Food security and forest access in the Colombian and Peruvian Amazon - Alexander Buritica; Martha Vanegas; Andres Espada; Mary Ngaiwi; Deborah Pierce; Marcela Quintero (Food Security, 2026)

Anti-inflammatory potential of diterpene-concentrated fractions from seaweed Dictyota menstrualis in zebrafish model - Johana Marcela Concha Obando; Juan P. García-López; Mario Caruffo; Thalisia Cunha dos Santos; Elisabete Barbarino; Guilherme Wolff Bueno; Valéria Laneuville Teixeira; Diana Negrão Cavalcanti; Cristian Reyes-Martínez; Katterine Astorga; Keinis Quintero; Carmen G. Feijóo (Algal Research, 2025)

Exploring the local nexus between human development and environmental sustainability: a case study from Colombia - Diego Valbuena; Daniel Gaitán-Cremaschi; Marcela Cely-Santos; Jose M. Ochoa-Quintero (Sustainability Science, 2025)
Evaluating the local nexus between human development (HD) and environmental sustainability (ES) can guide and inform policy and planning. This evaluation is particularly relevant in tropical countries, characterised by interactions among high biodiversity, monetary poverty, social inequalities, and environmental degradation. The aim of this paper is to analyse the HD–ES nexus across various municipalities in Colombia, situating the analysis within broader socio-economic structural patterns. We investigate the local diversity of the HD–ES nexus by creating a typology of municipalities, using selected and available socio-economic and environmental indicators through the combination of principal component analysis and non-hierarchical clustering analysis. Subsequently, we compare these municipal typologies against broader socio-economic structural variables by using regression analyses to better contextualise the diversity of local HD–ES nexus. We identify five distinct HD–ES types, including ‘Developed Degraded’, ‘Moderate Degraded’, ‘Poor Degraded’, ‘Moderate Modified’, and ‘Marginalised Preserved’. The location, characteristics, and context of these types are closely associated with the main geographical regions in Colombia, which also reflect the major settlement and development processes, including demographics, economic structure, accessibility, local government capacity, and armed conflict. We discuss how this diversity reflects the complexity in the interactions within this nexus, and the necessity for more targeted policy and planning to monitor and address these challenges. We suggest potential avenues for future research in balancing local human development and environmental sustainability in tropical countries.

The bittersweet economics of different cacao production systems in Colombia, Ecuador and Peru - Andrés Charry; Carolay Perea; Karen Ramírez; Guillermo Zambrano; Fredy Yovera; Adriana Santos; Tito Jiménez; Miguel Romero; Mark Lundy; Marcela Quintero; Mirjam Pulleman (Agricultural Systems, 2025)

Unraveling the chemistry of plant flammability: Exploring the role of volatile secondary metabolites beyond terpenes - Fabián Guerrero; Lorena Espinoza; Camilo Carmona; Melisa Blackhall; Carolina Quintero; Korina Ocampo-Zuleta; Susana Paula; Javier Madrigal; Mercedes Guijarro; Yulian Carrasco; Marcela A. Bustamante-Sánchez; Alejandro Miranda; et al. (Forest Ecology and Management, 2024)

Water temperature and microenvironmental factors predict the presence and detection of the snail host of Fasciola hepatica in Andean Patagonia - Ana C. Rodriguez Quinteros; Paula Soler; Marcela Larroza; Juan M. Morales; Juan M. Gurevitz (Veterinary Parasitology, 2024)

Applicability of a flood forecasting system for Nebraska watersheds - Sinan Rasiya Koya; Nicolas Velasquez Giron; Marcela Rojas; Ricardo Mantilla; Kirk Harvey; Daniel Ceynar; Felipe Quintero; Witold F. Krajewski; Tirthankar Roy (Environmental Modelling & Software, 2023)

Effects of human-induced habitat changes on site-use patterns in large Amazonian Forest mammals - Simón Quintero; Mark I. Abrahams; Christopher Beirne; John Blake; Elildo Carvalho; Hugo C.M. Costa; Milton José de Paula; Whaldener Endo; Torbjørn Haugaasen; Marcela Guimarães Moreira Lima; Fernanda Michalski; Diego Mosquera; et al. (Biological Conservation, 2023)

Correction: Research strategies to catalyze agroecological transitions in low- and middle-income countries - Sarah K. Jones; Nadia Bergamini; Francesca Beggi; Didier Lesueur; Barbara Vinceti; Arwen Bailey; Fabrice A. DeClerck; Natalia Estrada-Carmona; Carlo Fadda; Etienne M. Hainzelin; Danny Hunter; Chris Kettle; et al. (Sustainability Science, 2022)

Research strategies to catalyze agroecological transitions in low- and middle-income countries - Sarah K. Jones; Nadia Bergamini; Francesca Beggi; Didier Lesueur; Barbara Vinceti; Arwen Bailey; Fabrice A. DeClerck; Natalia Estrada-Carmona; Carlo Fadda; Etienne M. Hainzelin; Danny Hunter; Chris Kettle; et al. (Sustainability Science, 2022)
Governments are updating national strategies to meet global goals on biodiversity, climate change and food systems proposed in the Convention on Biological Diversity post-2020 framework and agreed at the United Nation’s Climate Change Conference (COP26) and Food Systems Summit (UNFSS). This represents a unique and crucial opportunity to integrate and accelerate food system actions to tackle interconnected global challenges. In this context, agroecology is a game-changing approach that can provide the world’s growing population with nutritious, healthy affordable food, ensure fair incomes to farmers and halt and reverse the degradation of the natural environment. Here, we explore agroecological transition pathways in four case studies from low- and middle- income countries and identify catalysts for change. We find that enabling policy and market environments, participatory action research and local socio-technical support each plays a critical role in stimulating transitions towards agroecology. We propose strategies and priorities for research to better support agroecological transitions using these catalysts of change as entry points. Engagement of governments, private sector, civil society, farmers and farm workers in this research agenda is essential.

Impact of initial explants on in vitro propagation of native potato (Solanum tuberosum, Andigena group) - Lenny Yojana Correa Mora; Daicy Yaneth Galvis Tarazona; María de los Angeles Bohórquez Quintero; Eyda Johanna Araque Barrera; Johan Sebastian Urquijo Ruíz; Diana Marcela Arias Moreno; Zaida Zarely Ojeda Pérez (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Diversity of cultivable bacteria from deep-sea sediments of the Colombian Caribbean and their potential in bioremediation - Lina Marcela Blandón; Mario Alejandro Marín; Marynes Quintero; Laura Marcela Jutinico-Shubach; Manuela Montoya-Giraldo; Marisol Santos-Acevedo; Javier Gómez-León (Antonie van Leeuwenhoek, 2022)

Action needed for staple crops in the Andean-Amazon foothills because of climate change - Lucila Marcela Beltrán-Tolosa; Carlos Navarro-Racines; Prajal Pradhan; Gisella S. Cruz-Garcia; Reynaldo Solis; Marcela Quintero (Mitigation and Adaptation Strategies for Global Change, 2020)

Changes in food access by mestizo communities associated with deforestation and agrobiodiversity loss in Ucayali, Peruvian Amazon - Genowefa Blundo-Canto; Gisella S. Cruz-Garcia; Elise F. Talsma; Wendy Francesconi; Ricardo Labarta; Jose Sanchez-Choy; Lisset Perez-Marulanda; Paula Paz-Garcia; Marcela Quintero (Food Security, 2020)
Few longitudinal studies link agricultural biodiversity, land use and food access in rural landscapes. In this paper, we test the hypothesis that, in a context of economic change, cash crop expansion is associated with deforestation, reduced agrobiodiversity and changes in food access. For this purpose, we analysed data collected from the same 53 upland and floodplain mestizo households in Ucayali, Peru, in 2000 and 2015. We found an emerging transition towards less diversified food access coupled with loss of forest cover and reduced agricultural biodiversity. In 2015, diets appeared to rely on fewer food groups, fewer food items, and on products increasingly purchased in the market compared to 2000. Wild fruits and plants were mentioned, but rarely consumed. Agricultural production systems became more specialised with a shift towards commercial crops. Peak deforestation years in the 15-year period appeared linked with incentives for agricultural expansion. Our results suggest an overall trend from diversified productive and “extractive” systems and more diverse food access, towards specialized productive systems, with less diverse food access and stronger market orientation (both in production and consumption). The assumption in the food and agricultural sciences that increased income and market-orientation is linked to improved food security, is challenged by our integrated analyses of food access, agrobiodiversity, land use and forest cover. Our results highlight the importance of longitudinal, multidimensional, systemic analyses, with major implications for land use, food and health policies. The potential risks of parallel homogenisation of diets and agricultural production systems require interdisciplinary research and policies that promote integrated landscape approaches for sustainable and inclusive food systems.

Four novel Talaromyces species isolated from leaf litter from Colombian Amazon rain forests - Neriman Yilmaz; Carlos A. López-Quintero; Aída Marcela Vasco-Palacios; Jens C. Frisvad; Bart Theelen; Teun Boekhout; Robert A. Samson; Jos Houbraken (Mycological Progress, 2016)